The Role of Non-Governmental Organizations in Achieving Sustainable Social Development In light of Vision 2030 : A Survey study of Workers in the Social Development Committees in Taif Governorate - Alghamdi, Ali Jamaan Sahlan (Journal of Humanities & Social Sciences, 2025)
The study aimed to identify the most important contributions of non-governmental organizations in achieving the (social - environmental - economic) dimension of sustainable development, as well as to identify the difficulties facing the work of non-governmental organizations in achieving sustainable social development. It also relied on the social survey method using the intentional sample method through a questionnaire prepared by the researcher and presented to arbitrators. The study sample consisted of (101) respondents who were collected electronically. The study data was collected during the year 2023. The results of the study concluded that the majority of the study sample members generally agree with the paragraphs of the axis of the contributions of non-governmental organizations in achieving the social dimension of sustainable development. The most important paragraphs of agreement were: Contributing to developing cultural awareness of the value of work and lawful earnings. The results also showed that the majority of the study sample members generally agree with the paragraphs of the axis of achieving the environmental dimension of sustainable development, which are: Playing an awareness-raising role on the importance of preserving water and not wasting it. The results also showed agreement on the axis of achieving the economic dimension of sustainable development, which is: Contributing to supporting productive families, and providing programs and activities that reduce unemployment. The results showed that the majority of the study sample members generally agree with Paragraphs of the axis of how to enhance the role of non-governmental organizations to achieve sustainable development in light of Vision 2030, and this is represented in implementing a variety of programs with social impact. The study recommended the necessity of coordination between non-governmental organizations in a way that works to find a formula for integration and interconnection between their roles and activities, and this includes the necessity of creating a degree of balance between the various services with a focus on development activities and programs in accordance with Vision 2030.
Keywords: Role; non-governmental organizations; sustainable social development; Vision 2030; Taif Governorate